Conference proceedings / XII. International Conference on Logistics in Agriculture 2018, [Novo mesto, Slovenia, 15 November 2018] - Marina Bajić; Lisec, Andrej (2018)
The 12th International Conference on Logistics in Agriculture, which has been organized by the Municipality of Sevnica, Grm Novo mesto - Biotechnology and Tourism Center, Faculty of Logistics, University of Maribor and Landscape Governance College GRM has this year's central theme Global Challenges of Logistics in agriculture. The conference has become traditional and paves the way for a different view of logistics in connection with agriculture. That's why we have invited lecturers on the topic Digitalization in Agriculture: Digital Revolution in Agriculture - Industry 4.0. In addition to this topic, we will also discuss the topic of advanced food packaging, analyse local food production, circular economy, food supply chain, modern city logistics, processing industry, sustainable food concept, optimization of production stages and wine logistics in Slovenia, delivery of locally grown food in the local environment with electric and hybrid vehicles and creative solutions in the logistics of the care and staying of the elderly.
Keywords: Logistics; agriculture; local food; packaging; electric vehicles